Validation of the Developed Innovative Supplemental Materials (ISMs) on the Least-learned Competencies in Grade 8 Physics - Paynandos, Jean Rose R. (Future Science / FSH-PH Publications, 2025)
The main objective of this study is to validate the developed innovative supplemental materials (ISMs) as instructional support in mastering the least-learned competencies (LLC) in eighth-grade physics. The study underwent planning, development, and validation phases. Planning involved identifying the LLC and creating five ISMs. In the development stage, ISMs were built using Microsoft PowerPoint and iSpring Suite 11, incorporating PhET simulations and interactive videos accessible online and offline. Validation involved three experts and 60 students from three schools in the Tago II District. Statistical tools like weighted mean and ANOVA were used for data analysis. The findings revealed that experts rated the ISMs